Habits: Plasticity, learning and freedom - Jose Ignacio Murillo (Frontiers Research Topics, 2015)
In present times, certain fields of science are becoming aware of the necessity to go beyond a restrictive specialization, and establish an open dialogue with other disciplines. Such is the case of the approach that neuroscience and philosophy are performing in the last decade. However, this increasing interest in a multidisciplinary perspective should not be understood, in our opinion, as a new phenomenon, but rather as a return to a classical standpoint: a proper understanding of human features -organic, cognitive, volitional, motor or behavioral, for example- requires a context that includes the global dimension of the human being. We believe that grand neuroscientific conclusions about the mind should take into account what philosophical reflection has said about it; likewise, philosophers should consider the organic constitution of the brain to draw inferences about the mind. Thus, both neuroscience and philosophy would benefit from each other's achievements through a fruitful dialogue. One of the main problems a multidisciplinary group encounters is terminology: the same term has a different scope in various fields, sometimes even contradictory. Such is the case of habits: from a neuroscientific perspective, a habit is a mere automation of an action. It is, therefore, linked to rigidity and limitation. However, from a classical philosophical account, a habit is an enabling capacity acquired through practice, which facilitates, improves and reinforces the performance of certain kind of actions. From neuroscience, habit acquisition restricts a subject's action to the learnt habit; from philosophy, habit acquisition allows the subject to set a distance from the simple motor performance to cognitively enrich the action. For example, playing piano is a technical habit; considering the neuroscientific account, a pianist would just play those sequences of keystrokes that had been repeatedly practiced in the past. However, according to the philosophical perspective, it would allow the pianist to improvise and, moreover, go beyond the movements of their hands to concentrate in other features of musical interpretation. In other words, a holistic view of habits focuses on the subject's disposition when facing both known and novel situations. We believe neuroscience could contribute to achieve a deeper understanding of the neural bases of habits, whose complexity could be deciphered by a philosophical reflection. Thus, we propose this Research Topic to increase our understanding on habits from a wide point of view. This collection of new experimental research, empirical and theoretical reviews, general commentaries and opinion articles covers the following subjects: habit learning; implicit memory; computational and complex dynamical accounts of habit formation; practical, cognitive, perceptual and motor habits; early learning; intentionality; consciousness in habits performance; neurological and psychiatric disorders related to habits, such as obsessive-compulsive disorder, stereotypies or addiction; habits as enabling or limiting capacities for the agent.